Prevalência e fatores associados à testagem para HIV entre as mulheres profissionais do sexo em Fortaleza - Martins, Telma Alves (2015)
Female sex workers (FSW) are recognized worldwide as a key population at higher risk of acquiring HIV infection. In Brazil, the prevalence of HIV in FSWs is 15 times higher than in the general Brazilian female population. This study aimed to identify factors associated with HIV testing among FSW resident in the city of Fortaleza, Ceará. A cross-sectional study using Respondent Driven Sampling (RDS) was conducted with 402 sex workers residing for at least three months in Fortaleza, 18 years of age or older and reporting having had sexual intercourse in exchange for money during the 4 previous months, was conducted from September to November 2010. Respondent Driven Sampling Analysis Tool version 6.0 and STATA version 11.0 were used. Non-ordinal multinomial logistic regression was conducted, with the outcome variable chosen was having been tested for HIV with <12 months. The variable "have tested" was tested with variables significant at p<0.20 in the multinomial analysis. The final model included the variables significant at p <0.05. The chance of FSWs to test longer than 12 months ago increased for older SWs (25-39), (OR = 2.57; 95% CI = 1, .09- 6,02), lower social class (OR = 2.71; 95% CI = 1,38- 5,30), separate / divorced or widowed women (OR = 4.27; 95% CI = 1.24 to 7, 51), living exclusively on prostitution (OR = 2.52; 95% CI = 1.21 to 5.27), not working in streets and squares (OR = 2.17; 95% CI = 1.03 to 4.58), having ≤1 client on the last day of work (OR = 6.81; 95% CI = 2.47 to 18.74), for those who said that the test should be mandatory for all people (OR = 2.30; 95% CI = 1.15 to 4.6) and those with knowledge about the transmission of HIV (OR = 3.95; 95% CI = 1.90 - 8.24). The chance of FSWs not testing increased for those who have not worked as SWs outside of Fortaleza (OR = 2.15; 95% CI = 1.83 to 9.97) for those who had ≤1 client on the last day of work (OR = 6.64; 95% CI = 2.23 to 19.8), for those claiming to have moderate / high chance of becoming infected with HIV (OR = 2.18; 95% CI = 1.04 4.53), for those who said that the test should be mandatory for all people (OR = 2.43; 95% CI = 1.22 to 4.85), and for those unaware of the sites of free testing (OR = 4.41; 95% CI = 2,01- 9,69). The FSWs accessed in the study demonstrate high HIV prevalence, exposure to numerous risk factors, and that do not get tested for HIV with appropriate frequency. Health Policies need to be more effective in meeting the occupational demands of FSWs to be able to reduce their individual, social and programmatic vulnerabilities.